Improving generic skills among engineering students through project-based learning in a project management course - Guerrero Chanduví, Dante A. (2013)
The speed of technological change, the increase in social exigencies, and the need to take good care of the environment, has made evident that engineering graduates must have generic skills of a holistic nature in order to successfully meet future professional challenges. This paper explains the impact of a project-based learning methodology on the improvement of generic skills. The methodology was used in an undergraduate industrial engineering project management course. Measurements of student knowledge and mastery of technical, contextual and behavioral skills were performed at the beginning and end of the course. Written questionnaires that measured the three dimensions were employed; the collected data was used in a statistical and a consistency analysis. The results indicate a significant improvement in student skills that can be attributed to the use of project based learning (PBL). It is known that PBL is only one of the many possible ways to improve generic skills, but it is a powerful tool that balances and complements an engineering curriculum that strives to develop the generic skills of engineering students.